Bandwidth and gain enhancement of a circular microstrip antenna using a DNG split ring resonator radome - Rasheed, Ojo; M. F., Jamlos; Ping, Jack Soh; Mohd Aminudin, Jamlos; Muammar, Mohamad Isa (IAES, 2019)
This paper present the design of a circular patch microstrip antenna with enhancement in terms of bandwidth and gain using a dielectric double negative (DNG) split ring metamaterial radome. This radome is positioned on top of the CP antenna operating from 5.2 GHz to 6.4 GHz. The metamaterial radome comprises of two alternate split rings of negative permittivity, permeability and refractive index. The circular microstrip antenna bandwidth of 430 MHz has been realized by the presence of DNG metamaterial radome compared to 220 MHz without the radome. The gain has been increased as well from 1.84 dBi to 3.87 dBi.